2021
DOI: 10.1016/j.dsx.2021.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis in COVID-19

Abstract: Background and aims Initially, novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) was considered primarily a respiratory pathogen. However, with time it has behaved as a virus with the potential to cause multi-system involvement, including neurological manifestations. Cerebral venous sinus thrombosis (CVT) has increasingly been reported in association with coronavirus infectious disease of 2019 (COVID-19). Here, we have shed light upon CVT and its possible mechanisms in the backdrop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 104 publications
1
40
0
2
Order By: Relevance
“…For COVID-19 infections, the time frame in our cohort was 60-80 days. Indeed, the time from COVID symptoms to CVT reported by other authors is estimated to be between 1-2 weeks 18, 19 . The occurrence of CVTs would precede the diagnosis of bDAVFs in up to 6 months, which agrees with our ndings.…”
Section: Discussionmentioning
confidence: 90%
“…For COVID-19 infections, the time frame in our cohort was 60-80 days. Indeed, the time from COVID symptoms to CVT reported by other authors is estimated to be between 1-2 weeks 18, 19 . The occurrence of CVTs would precede the diagnosis of bDAVFs in up to 6 months, which agrees with our ndings.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have found a significant association between COVID-19 and CVT [11] , [12] , [15] , [16] , [17] . In this study, we reviewed our multi-center experience with CVT during the current COVID-19 pandemic with a primary focus on the patients’ presentation, management, and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, reports of patients presenting with CVT following COVID-19 vaccination have suggested a potential association between CVT and this preventive practice [11] , [12] , [13] . Although multiple studies have looked at CVT in COVID-19 patients [10] , [11] , [12] , [14] , [15] , [16] , [17] , [18] , [19] , the influence of COVID infection or vaccination in patients presenting with CVT and their potential manifestations is understudied. We aim to describe the clinical and radiographic characteristics, as well as management and outcomes of CVT in patients with a prior COVID infection or vaccination who were treated at our institutions during the COVID pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of COVID-19 patients requiring ICU stay, it was noted that the rate of thrombotic disorders in these patients was 31% [ 7 ]. Furthermore, images have shown that 27% of such thrombotic disorders are due to venous thromboembolism, 3.7% due to arterial thrombosis, and 81% due to pulmonary embolism [ 7 ].…”
Section: Discussionmentioning
confidence: 99%